Inorganic engineered nanoparticles in drinking water treatment: a critical review. Issue 1 (2nd September 2015) - Simeonidis, Konstantinos; Mourdikoudis, Stefanos; Kaprara, Efthimia; Mitrakas, Manassis; Polavarapu, Lakshminarayana
Abstract : This review summarizes the recent research in the field of inorganic engineered nanoparticle development with direct or potential interest for drinking water treatment. Abstract : This review summarizes the recent research in the field of inorganic engineered nanoparticle development with direct or potential interest for drinking water treatment. The incorporation of engineered nanoparticles into drinking water treatment technologies against the removal of heavy metals, microorganisms and organic pollutants appears as a very dynamic branch of nanotechnology. Nanoparticles owe their potential to the high specific surface area and surface reactivity compared to conventional bulk materials. Depending on the mechanism of uptake, nanoparticles can be designed to establish high selectivity against specific pollutants and provide the required efficiency for application. However, despite early encouraging results, nanoparticles meet a number of limitations to get promoted and become part of large-scale water treatment plants. The most important is their availability in the required large quantities and their efficiency to fulfil the strict regulations for drinking water consumption and environmental safety. Both deal with the particle preparation cost and the cost of treatment operation with respect to the increase in supplied water price for the consumers. Under this view, this work attempts to evaluate reported studies according to their possibility to meet the reliable requirements of water technology and also suggests an experimental approach to allow validation of tested nanoparticles.